Evaluation of diagnostic accuracy of urine neutrophil gelatinase-associated lipocalin in patients with symptoms of urinary tract infections: a meta-analysis - Zhang, Yin; Chen, Chen; Mitsnefes, Mark; Huang, Bin; Devarajan, Prasad (Frontiers in Pediatrics, 2024)
Early and accurate diagnosis of urinary tract infection (UTI) can prevent serious sequelae including chronic kidney disease. Multiple individual studies have identified urine neutrophil gelatinase-associated lipocalin (uNGAL) as a promising biomarker for early diagnosis of UTI. We sought to understand the distribution and diagnostic accuracy of uNGAL values in patients presenting with UTI symptoms. Our systematic literature reviews identified studies reporting mean, standard deviation, quartiles, and upper and lower detection limits of uNGAL in symptomatic patients with and without culture-confirmed UTI. Out of 25 identified studies, 17 were in children. Meta analyses were performed using the quantile estimation (QE) method estimating the distributions of uNGAL, which were then compared between the two groups for identifying the best cut-off points maximizing the Youden index. We found that uNGAL levels were significantly higher in samples with confirmed UTI compared to those without. In pediatric studies, median and 95% confidence interval (CI) of uNGAL values are 22.41 (95% CI of 9.94, 50.54) ng/mL in non-UTI group vs. 118.85 (95% CI of 43.07, 327.97) ng/mL in UTI group. We estimated the cut-off point of 48.43 ng/mL with highest sensitivity (96%) and specificity (97%) in children. Sensitivity analysis including both pediatric and adult studies yielded similar results. Our results confirm that uNGAL can accurately distinguish patients with and without confirmed UTI among symptomatic patients. We also confirm that the range of uNGAL concentrations and cut-off points reported in subjects with UTI is much lower than that reported in patients with acute kidney injury.